NIAT KONSUMEN TERHADAP PENGGUNAAN E-COMMERCE DI KABUPATEN ROKAN HULU - Putri Maurisni; Nanda Rahmadi Pratama (Jurnal Bina Wira, 2024)
As technology and communication develop, people are now getting closer to technology. This turned out to have a big impact on people's lives, especially the people of Rokan Hulu Regency. One very clear impact is in the business world where there are marketing activities. Currently, there are many SMEs and even companies that run their businesses using internet technology. With internet technology, it makes it easy for them to cover more consumers. Furthermore, this has an impact on the behavior of the people of Rokam Hulu Regency in shopping to meet their needs. This study provides insight into how the people of Rokan Hulu Regency behave towards Ecommerce transactions. This study presents a conceptual framework based on the Technology Acceptance Model (TAM). For data analysis, the Partial Least Squares (PLS) method was used by collecting data from 129 respondents. The research results show that there is a positive and significant influence of perceived usefulness, perceived ease of use, and social influence on E-Commerce transaction behavior. These results are very important for businesses, marketers and online merchants.